Effect of Passenger Physical Characteristics in the Uptake of Combustion Products during a Railway Tunnel Evacuation Due to a Fire Accident - Thomas Zisis; Konstantinos Vasilopoulos; Ioannis Sarris (Computation, 2023)
The current study examines how different types of passengers (elders, travelers with luggage, travelers without luggage, and mixed population) affect the evacuation process in railway tunnels after a fire accident based on Fractional Effective Dose (FED) index values. A 20 MW diesel pool fire in an immobilized train located inside a straight, rectangular railroad tunnel that is ventilated by a longitudinal jet fan ventilation system is the scenario under consideration. Two fire scenarios were examined, one with and one without ventilation, combined with four evacuation scenarios. The numerical simulation of the fire and the evacuation process is conducted with the Fire Dynamics Simulator and Evacuation code (FDS + Evac) which is a Large Eddy Simulator (LES) for low-Mach thermally driven flows. The results (evacuation times, walking speeds, and mean and max FED values) are compared for each passenger type. It is found that during the evacuation from a railway tunnel fire accident, the most affected population are the elderly because of their lower movement speed, and travelers with luggage because of their increased dimensions. It is also shown that a non-homogenous population has increased uptake of combustion products and longer evacuation times than a homogenous population with similar geometrical characteristics.